A cost analysis of treating postoperative periprosthetic femoral fractures following hip replacement surgery in a UK tertiary referral centre. Issue 2 (February 2023) - Jain, S.; Menon, D.; Mitchell, T.; Kerr, J.; Bassi, V.; West, R.; Pandit, H.
Highlights: Treatment costs of periprosthetic femoral fracture (PFF) are high and there is inadequate reimbursement through NHS tariff. The highest costs are associated with ward stay, theatre utilisation and overheads. In our unit there was no difference in cost between open reduction and internal fixation and revision surgery. Abstract: Aim: This study aims to evaluate costs associated with periprosthetic femoral fracture (PFF) treatment at a UK tertiary referral centre. Methods: This study included 128 consecutive PFFs admitted from 02/04/2014–19/05/2020. Financial data were provided by Patient Level Information and Costing Systems. Primary outcomes were median cost and margin. Secondary outcomes were length of stay, blood transfusion, critical care, 30-day readmission, 2-year local complication, 2-year systemic complication, 2-year reoperation and 30-day mortality rates. Statistical comparisons were made between treatment type. Statistical significance was set at p <0.05. Results: Across the cohort, median cost was £15, 644.00 (IQR £11, 031.00-£22, 255.00) and median loss was £3757.50 (£599.20-£8296.20). The highest costs were ward stay (£3994.00, IQR £1, 765.00-£7, 013.00), theatre utilisation (£2962.00, IQR £0.00-£4, 286.00) and overheads (£1705.10, IQR £896.70-£2432.20). Cost (£17, 455.00 [IQR, £13, 194.00-£23, 308.00] versus £7697.00 [IQR £3871.00-£10, 847.00], p <0.001) and loss (£4890.00 [IQR £1308.00-£10, 009.00] versus £1882.00 [IQR £313.00-£3851.00], p = 0.02) were greater in the operative versus the nonoperative group. There was no difference in cost (£17, 634.00 [IQR £12, 965.00-£22, 958.00] versus £17, 399.00 [IQR £13, 394.00-£23, 404.00], p = 0.98) or loss (£5374.00 [IQR £1950.00-£10, 143.00] versus £3860.00 [IQR -£95.50-£7601.00], p = 0.21) between the open reduction and internal fixation (ORIF) and revision groups. More patients required blood transfusion in the operative versus the nonoperative group (17 [17.9%] versus 0 [0.0%], p = 0.009). There was no difference in any clinical outcome between the ORIF and revision groups ( p >0.05). Conclusion: PFF treatment costs are high with inadequate reimbursement from NHS tariff. Work is needed to address this disparity and reduce hospital costs. Cost should not be used to decide between ORIF and revision surgery.